A toxicological assessment of Hericium erinaceus (Lion’s mane) and Trametes versicolor (Turkey tail) mushroom powders - Mahadevan, Kritika; Daoust, Julie; Brendler, Thomas; Chaudhary, Ankit; Saifi, Alimuddin; Garg, Vipin Kumar (Frontiers in Toxicology, 2025)
Hericium erinaceus (Lion’s mane) and Trametes versicolor (Turkey Tail) mushrooms have an extensive history of use in traditional medicine and as food. Oftentimes, they are available as extract preparations produced from selected life stages such as fruiting body or mycelium. Their composition may vary based on where they are grown and the conditions of post-harvest preparation. Despite their widespread traditional use and popularity, comprehensive toxicological assessments, particularly of whole mushroom powders, remain limited. This study was conducted to evaluate whether the commercially available Organic Lion’s Mane M2-102-10 powder (H. erinaceus mycelial biomass and fruiting body cultured on oats) and Organic Turkey Tail M2-101-03 powder (Trametes versicolor mycelial biomass and primordia cultured on oats) cause acute toxicity, subchronic toxicity, and genotoxicity in rats. The tests were carried out in accordance with OECD guidelines. The results demonstrated that both Organic Lion’s Mane M2-102-10 powder and Organic Turkey Tail M2-101-03 powder did not induce acute toxicity, showed no evidence of subchronic oral toxicity in rats at doses up to 2000 mg/kg body weight/day, and exhibited no genotoxicity in either in vitro or in vivo assays.